(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: Everyone has certain characteristics that set them apart from others. Variations in the palatal rugae pattern is one such feature which stay consistent throughout one's life specially edentulous patients. So, this rapidly emerging branch of forensic odontology can be taken as an adjuvant in investigation of criminals which has immense significance in giving more accuracy.Aim: The current study aims to compare distinctiveness of the palatal rugae in gender of various age and to investigate if the specific palatal rugae pattern may be utilised as a strategy for sex estimation.Methods: Model casts of 200 people were created, segregated & the prominent elevations on both the sides of median palatal raphae was analysed. The statistical analysis to compare the proportions was presented. Result: Wavy rugae patterns are more prevalent in males whereas curved rugae patterns in females.Conclusion: Association of palatal rugae behold the potential key in establishing the person’s sex which is crucially importance.